The Micro Basis of Budget System Reform : The Case of Transitional Economies - Diamond, Jack (IMF Working Papers; Working Paper ;, 2002)
In reviewing the means to strengthen public expenditure management (PEM) systems, there has been increased emphasis on the micro basis of broader budget system reforms, especially reforms of the internal financial management systems in government agencies. Specifically in transition economies, there has been increasing recognition that OECD-type budget systems need to be broadly based on a firm platform of financial management in government institutions. At the same time, many transitional countries have generally acknowledged that this aspect of their PEM systems is problematic and needs to be rectified; hence, international agencies have been actively promoting reforms in these areas. In particular, three areas have been emphasized: human resource management, procurement, and internal audit. This paper explores the problems faced by transitional economies in each of these areas and reviews the generally recommended solutions to these problems.